Effects of Different Quenching Treatments on Thermal Properties and Microstructure in Quaternary Cu-Based HTSMA - Dagdelen, F.; Kanca, M. S.; Kok, M. (Pleiades Publishing Ltd, 2019)
In this study, some physical properties of a quaternary Cu-based alloy have been studied on the example of the alloy Cu-13Al-4.5Ni-1.5Ti (wt %) that was produced by using the arc-melting method. Four specimens were made from the alloy ingot, and three of them were subjected to heat treatment at 930 degrees C for 30 min. Later, they were separately quenched into liquid nitrogen (-196 degrees C), alcohol (0 degrees C), and iced-brine (6 degrees C) mediums. Differential Scanning Calorimetry (DSC) measurements of all samples were performed to determine the effect of quenching on the phase transformation temperatures. It was observed that the quaternary Cu-Al-Ni-Ti alloy is a high temperature shape memory alloy (HTSMA) and its transformation temperatures significantly were affected by heat treatments, e.g., the phase transformation temperatures increased via quenching in alcohol and iced brine by approximately 100 K. Moreover, optical microscopy (OM) and Scanning Electron Microscopy (SEM) images were taken to observe the changes in the microstructure after heat treatment. It was revealed that grain boundaries were more discernable in the samples that were quenched in alcohol and iced brine, also the volume fraction of martensite plates was increased. Crystal structures of samples at room temperature were determined by using X-ray diffractograms, whereby, the pattern showed the presence of beta', gamma(2), and X phases, which are of martensite origin.
Keywords: shape memory alloy; transformation temperature; martensite phase